Exploding heads, doing school and intangible work: an ethnographic case study of first year education doctoral students becoming education researchers - Meyer-Parsons, Beatrice, author; Banning, James, advisor; MacPhee, David, advisor; Kees, Nathalie, committee member; Most, David, committee member (Colorado State University. Libraries, 2011)
There is limited research concerned with how education doctoral students become education researchers, what Labaree (2003) described as "the peculiar problems of preparing education researchers." This is an ethnographic case study of a cohort of first year education doctoral students in a qualitative research classroom for the purpose of better understanding how they are becoming education researchers and "scholars of the discipline," able to guide both practice and policy. In this study, students described feeling met by the instructor with respect and developing new perspectives and actions by taking on the role of qualitative researcher. However, students also described experiencing "exploding heads" as they attempted to meet time constraints, competing demands within the program and in connection with commitments to family, work and other, personal projects. Within this culture of contradictions students engaged in strategies to manage their "exploding heads": they were "doing school" and "doing the intangible work" of becoming education researchers by strategies of self. "Getting the work done" and meeting instructor requirements were ways of "doing school". Negotiating commitments and resources (e.g., time away from family); making schoolwork "personal"; identifying as "certain kinds of people" (e.g., teacher); and/or identifying/dis-identifying with other students, faculty or valued persons were strategies of the self. Based on these students' descriptions, an ecological typology of students was developed: "savvy" students (who were "doing school"); "working from the self" students (who were actively fashioning selves); and "disconnecting students." For (future) education doctoral students the study suggests possible challenges, such as the ability to value contradictions as opportunities for expanding perspectives and taking new actions, as well as the need to actively engage in the intangible work of finding means for continuity and confirmation of self. In terms of classroom teaching, an action, paradoxical pedagogy is suggested to provide a "becoming space," an ecology that can create opportunities out of contradictions. From an organizational perspective the study suggests that schools of education consider curriculum, program requirements and faculty talk as areas to provide messages and niches for students who are actively looking to identify and connect their selves while becoming education researchers.
Keywords: doing school; self; ethnography; education researcher